Uterine artery Doppler study for the prediction and the severity of the hypertensive disorders during pregnancy - Chakraborty, Saptarshi; Saharan, Surabhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorder in pregnancy is one of the major cause of maternal and perinatal mortality and morbidity worldwide particularly in developing countries. In developed countries, maternal mortality rate varies from 4-40 per 1 lakh live birth. In developing countries, it varies from 100-700 with India having 178 per 1 lakh live birth. Objectives were to study of uterine artery Doppler for the prediction of hypertensive disorders and its severity, Sensitivity and Specificity of Uterine Artery Doppler and their comparison for the prediction and the severity of hypertensive disorders during pregnancy. Methods: This is a prospective study. Approximately hundred patients with hypertensive disorders during pregnancy attending the OPD and IPD in Obstetrics and Gynecology Department will be included. All the patients in this study group will be subjected to Ultrasonographic evaluation of the pregnancy along with the Arterial Doppler of both the Uterine Artery and Umbilical Artery will be done. Results: Using uterine artery Doppler Study in combination is significantly useful in early prediction of PIH having specificity and sensitivity of Uterine artery Doppler study – Pi Index as 91.67% and 85.71 %, Ri Index as 87.5% and 71.43% and diastolic notch as 94.44% and 92.85 % respectively. The use of uterine artery Doppler Study as an important tool for early prediction of PIH and has a lot of prognostic value. Conclusions: The predictive accuracy of uterine artery Doppler study using Pi Index and Ri Index is better in the detection of early-onset PIH, than the late-onset disease. Thereby, it will help in the long run to prevent the increasing maternal and fetal morbidity and mortality.